Maintenance of Barrier Tissue Integrity by Unconventional Lymphocytes - Cox, Joshua R.; Cruickshank, Sheena M.; Saunders, Amy E. (Frontiers in Immunology, 2021)
Mucosal surfaces, as a first barrier with the environment are especially susceptible to damage from both pathogens and physical trauma. Thus, these sites require tightly regulated repair programs to maintain barrier function in the face of such insults. Barrier sites are also enriched for unconventional lymphocytes, which lack rearranged antigen receptors or express only a limited range of such receptors, such as ILCs (Innate Lymphoid Cells), γδ T Cells and MAIT (Mucosal Associated Invariant T Cells). Recent studies have uncovered critical roles for unconventional lymphocytes in regulating mucosal barrier function, and, in particular, have highlighted their important involvement in barrier repair. The production of growth factors such as amphiregulin by ILC2, and fibroblast growth factors by γδ T cells have been shown to promote tissue repair at multiple barrier sites. Additionally, MAIT cells have been shown to exhibit pro-repair phenotypes and demonstrate microbiota-dependent promotion of murine skin healing. In this review we will discuss how immune responses at mucosal sites are controlled by unconventional lymphocytes and the ways in which these cells promote tissue repair to maintain barrier integrity in the skin, gut and lungs.